2008
DOI: 10.1111/j.1741-3737.2008.00479.x
|View full text |Cite
|
Sign up to set email alerts
|

Life Course Transitions and Housework: Marriage, Parenthood, and Time on Housework

Abstract: We examine the effects of transitions in marital and parenthood status on 1,091 men's and women's housework hours using two waves of data from an Australian panel survey titled Negotiating the Life Course. We examine transitions between cohabitation and marriage, and from cohabitation or marriage to separation, as well as transitions to first and higher-order births. We find extraordinary stability in men's housework time across most transitions but considerable change for women in relation to transitions in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
407
1
17

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 438 publications
(452 citation statements)
references
References 34 publications
27
407
1
17
Order By: Relevance
“…The transition to parenthood is a major life-course transition that (i) is experienced sooner or later by a majority of people and (ii) has a transformative effect on people's lives by shifting goals, identity and resources such as time and income. Additionally, sociological research has demonstrated that the transition to parenthood is associated with the onset of gender inequalities in, amongst others, paid and unpaid work, leisure and sleep time, and mental health (Baxter et al 2008;Budig and England 2001;Craig and Mullan 2013;Kaufman and Uhlenberg 2000;Singley and Hynes 2005;Wheaton 1990). …”
Section: Introductionmentioning
confidence: 99%
“…The transition to parenthood is a major life-course transition that (i) is experienced sooner or later by a majority of people and (ii) has a transformative effect on people's lives by shifting goals, identity and resources such as time and income. Additionally, sociological research has demonstrated that the transition to parenthood is associated with the onset of gender inequalities in, amongst others, paid and unpaid work, leisure and sleep time, and mental health (Baxter et al 2008;Budig and England 2001;Craig and Mullan 2013;Kaufman and Uhlenberg 2000;Singley and Hynes 2005;Wheaton 1990). …”
Section: Introductionmentioning
confidence: 99%
“…The earning and allocation of household income is still gendered (Baxter et al 2008;Himmelweit 2002;Stotsky 1996, p. 14), and studies of gendered spending patterns over the past 20 years have consistently shown that household finances should not be regarded as pooled funds (see, for example, Sonnenberg et al 2011). A gender impact analysis of intra-household finances will examine not only who earns the money, but how financial resources are managed and controlled.…”
Section: Broad-based Consumption Taxmentioning
confidence: 99%
“…We therefore adopt an instrumental variable (IV) approach (see Mundlak, 1978;Skrondal andRabe-Hesketh, 2004 andBaxter et al 2008) …”
Section: Data and Samplementioning
confidence: 99%